2015
DOI: 10.5114/pg.2015.49107
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stoma in patients with colorectal cancer from the perspective of 20-year period of clinical observation

Abstract: IntroductionIntestinal stoma is a procedure most often performed in patients with colorectal cancer.AimTo identify the percentage of patients with colorectal cancer in which the intestinal stoma was performed.Material and methodsWe retrospectively analysed 443 patients treated during a 20-year period (1994–2013) due to colorectal cancer, in which the intestinal stoma was made during the first surgical intervention.ResultsIn the second analysed decade, a significant decrease in the percentage of created stomas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…In terms of the socioeconomic impact of such programmes, early detection provides for far more flexible treatment options [78]. Patients are also more likely to have a temporary stoma than a permanent stoma if their colon cancer was diagnosed at an early stage [80]. Earlier diagnosis would therefore allow more patients to maintain/retain a normal lifestyle for longer.…”
Section: Future Directions and Discussionmentioning
confidence: 99%
“…In terms of the socioeconomic impact of such programmes, early detection provides for far more flexible treatment options [78]. Patients are also more likely to have a temporary stoma than a permanent stoma if their colon cancer was diagnosed at an early stage [80]. Earlier diagnosis would therefore allow more patients to maintain/retain a normal lifestyle for longer.…”
Section: Future Directions and Discussionmentioning
confidence: 99%
“…In their study, Banaszkiewicz et al analyzed 1710 patients who were operated for colorectal cancer over a 20-year period and they reported that stoma was formed in one third of the patients. Furthermore; in this study, 230 cases have undergone emergency surgery and it has been reported that the patients who have been operated under emergency conditions have had a higher rate of stomata opening than the patients operated under elective conditions [5] .…”
Section: Discussionmentioning
confidence: 80%
“…The preference of loop ileostomy, colostomy and hartmann procedure may vary according to the indication and surgeon. In emergency surgery, the stoma which is opened for sepsis control may be life-saving [4,5] . The aim of this study was to discuss the ostomy indications, stoma preferences and the early stage results of these operations.…”
Section: Introductionmentioning
confidence: 99%
“…Radical resection is the major therapy for non-metastatic and resectable metastatic CRC patients. However, nearly 15% CRC patients require simultaneous temporarily ileostomy to reduce anastomotic leakage risk [6,7]. In general, rectal cancer patients who underwent neoadjuvant radiotherapy occupy the largest percentage in these patients, as preoperative radiotherapy was reported to increase anastomotic leakage risk [8].…”
Section: Introductionmentioning
confidence: 99%